A Role for Estrogen in Schizophrenia: Clinical and Preclinical Findings - Andrea Gogos; Alyssa M. Sbisa; Jeehae Sun; Andrew Gibbons; Madhara Udawela; Brian Dean (International Journal of Endocrinology)
Gender differences in schizophrenia have been extensively researched and it is being increasingly accepted that gonadal steroids are strongly attributed to this phenomenon. Of the various hormones implicated, the estrogen hypothesis has been the most widely researched one and it postulates that estrogen exerts a protective effect by buffering females against the development and severity of the illness. In this review, we comprehensively analyse studies that have investigated the effects of estrogen, in particular 17β-estradiol, in clinical, animal, and molecular research with relevance to schizophrenia. Specifically, we discuss the current evidence on estrogen dysfunction in schizophrenia patients and review the clinical findings on the use of estradiol as an adjunctive treatment in schizophrenia patients. Preclinical research that has used animal models and molecular probes to investigate estradiol’s underlying protective mechanisms is also substantially discussed, with particular focus on estradiol’s impact on the major neurotransmitter systems implicated in schizophrenia, namely, the dopamine, serotonin, and glutamate systems.